若a-b=-1,ab=3,求a^3b-2a^2b^2+ab^3的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 17:23:31
若a-b=-1,ab=3,求a^3b-2a^2b^2+ab^3的值若a-b=-1,ab=3,求a^3b-2a^2b^2+ab^3的值若a-b=-1,ab=3,求a^3b-2a^2b^2+ab^3的值a
若a-b=-1,ab=3,求a^3b-2a^2b^2+ab^3的值
若a-b=-1,ab=3,求a^3b-2a^2b^2+ab^3的值
若a-b=-1,ab=3,求a^3b-2a^2b^2+ab^3的值
a-b=-1,ab=3,
a^3b-2a^2b^2+ab^3
=ab(a^2-2ab+b^2)
=ab(a-b)^2
=3*(-1)^2
=3
a^3b-2a^2b^2+ab^3
=ab(a^2-2ab+b^2)
=ab(a-b)^2
=3*(-1)^2
=3*1
=3
若a-b=4,ab=1,求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)的值
若a-b=4 ab=1 求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)的值
若a-b=4 ab=1 求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)的值
若a/b+b/a=3,求a^2+ab+b^2/a^2-ab+b^2的值
已知a,b满足a+b=5,a-b=1,求ab,a^2+b^2-3ab
若a+b=3,ab=1 求a^3b+ab^3和(a-b)^2的值
若a+b=3 ab=-2,求a+ab+ab+b的值
若ab不等于0,且3a=b,求代数式b/3a-(-b)/a-a/2b/(-b)
若a+b=3,ab=-2,求(5a-5b-ab)-(4a-6b-3ab)
已知a-b=-1,ab=-2,求代数式(3a-4b-ab)-(a-2b+3ab)
若a-b=3ab,求2a-ab-2b除以a+2ab-b的值
已知a-b=2,ab=-1 求(4a-5b-ab)-(2a-3b-5ab)
已知b=a(2b 1),求3a ab-3b/a-3ab-b的值.快
已知a-b=4,ab=-1,求(-2ab+2a+3b)-(a-4b+b)
若A=a+2b B=-b+3a 求2AB
已知a+b=A,ab=A+2008,1-2(a+ab)+(ab-2b)=3A.求a+b和ab的值
已知a+b=A ab=A+2008 1-2(a+ab)+(ab-2b)=3A 求a+b ab的值
已知a+b=A ab=A+2008 1-2(a+ab)+(ab-2b)=3A 求a+b ab的值